1984
DOI: 10.1038/bjc.1984.111
|View full text |Cite
|
Sign up to set email alerts
|

Childhood lymphoblastic leukaemia: Sex difference in 6-mercaptopurine utilization

Abstract: Summary Twelve boys and 10 girls on similar long term remission maintenance treatment for lymphoblastic leukaemia had 79 random assays of their red cell 6 thioguanine nucleotide (6TGN) concentrations performed as an index of cytotoxic activity generated by oral 6-mercaptopurine (6MP).Correlation between the dose of 6MP and 6TGN was statistically significant in the girls (r=0.58, P<0.001) but not in the boys (r=0.15). Additionally, as a group the boys tolerated more 6MP (P<0.05), despite similar prescribing cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
(7 reference statements)
1
10
1
Order By: Relevance
“…It suggests a sex‐linked genetic polymorphism present in the degradation pathways of 6‐TG leading to the accumulation of sinusoidal toxic metabolites in the liver. So far, these pathways remain uncharacterized and speculative (Lilleyman et al , 1984). Given the gender bias, predictably TPMT activity does not predispose to the development of VOD; however, neither does the dose of thiopurine administered nor the red cell intracellular concentration of TGNs.…”
Section: Resultsmentioning
confidence: 99%
“…It suggests a sex‐linked genetic polymorphism present in the degradation pathways of 6‐TG leading to the accumulation of sinusoidal toxic metabolites in the liver. So far, these pathways remain uncharacterized and speculative (Lilleyman et al , 1984). Given the gender bias, predictably TPMT activity does not predispose to the development of VOD; however, neither does the dose of thiopurine administered nor the red cell intracellular concentration of TGNs.…”
Section: Resultsmentioning
confidence: 99%
“…Higher methylated metabolite levels in women versus men were also reported in a large patient population. 32,42 Boys tolerated higher doses of MP than girls on the same prescribing criteria and might develop myelotoxicity less readily and less predictably than girls. Because high 6-MeMPN levels are associated with hepatotoxicity 15 and myelotoxicity, 26 girls may develop AZAinduced hepatotoxicity and myelotoxicity more readily than boys, and so close attention should be paid in monitoring drug concentrations, hematological, and hepatic parameters in thiopurine-treated girls with IBD.…”
Section: Discussionmentioning
confidence: 97%
“…24 However, that study 22 reported that women formed more 6-TGN levels than men, whereas gender did not predict 6-TGN levels in this study. 32 Sex and age at diagnosis were reported as independent variables associated with the risk of relapse in children with acute lymphoblastic leukemia 42 and patients with CD 33 during thiopurine therapy. Sex differences in thiopurine metabolism were preliminarily described in children with acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boys seem to tolerate 6-mercaptopurine better than girls, inasmuch as cytotoxicity develops at lower doses and more predictably in girls than in boys. [34][35][36][37] It has been speculated that pharmacokinetic mechanisms could be the cause for the higher relapse rate of ALL in boys than in girls. Several studies on gender-related differences in RBC TPMT activity have reported higher activities of male subjects in adult population samples.1,3,10,38 In healthy children CLINICAL P HARMACOLOGY &THERAPEUTICS JULY 1996 from 1 to 10 years old, Klemetsdal et at.32 found only minor and nonsignificantly higher RBC TPMT activity in boys than in girls (11.1 units [n = 871 versus 10.6 units [n = 711).…”
Section: Discussionmentioning
confidence: 99%